Analysis of the correlation between critical thinking and metacognitive skills of senior high school students in biology Jeneponto Regency, South Sulawesi, Indonesia - Saleh , Rahmat; Filawati, Filawati; Adriani, Adriani; Andariana , Andi (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2023)
There is a need to map the connection between critical thinking and metacognitive skills of high school students so that educators can determine learning steps to help students obtain optimal learning outcomes and 21st-century skills. The research objective is to Examine the relationship between high school biology students' metacognitive abilities and critical thinking education. It is a quantitative-correlational study. The research sample was 230 grade XI students pursuing science specialization obtained by purposive random sampling from Jeneponto Regency, South Sulawesi, Indonesia. The research instrument used is an examination formatted as an essay that has been confirmed by professionals. The research data is the value of critical thinking and metacognitive skills from the results of taking tests in the form of essays. The method of data analysis was used through linear regression analysis using SPSS 23 for Windows. The study's findings indicate a strong correlation between critical thinking and metacognitive abilities of high school students in biology education with a significance value of 0.000 (p ˂ 0.05). It can be seen that critical thinking skills contribute 68.6% to students' metacognitive skills. Therefore, this research finds that there is a substantial correlation between high school biology students' metacognitive abilities and critical thinking. Teachers can use the research findings to identify instructional strategies that foster critical thinking in order to help students become more independent and metacognitive.